JINR activity in microwave sources for TeV range linear colliders - Elzhov, A.V.; Ivanov, I.N.; Kaminsky, A.K.; Kazacha, V.I.; Perelstein, E.A.; Sedykh, S.N.; Sergeev, A.P.; Denisov, G.G.; Ginzburg, N.S.; Peskov, N.Yu.; Sergeev, A.S.; Laziev, E.M. (Вопросы атомной науки и техники, 2000)
Results of theoretical and experimental studies of the microwave radiation sources on the base of the induction linac LIU-3000 (JINR, Dubna) are presented. In particular, a FEM-oscillator with the reversed guide magnetic field and Bragg resonator as well as an electron beam buncher in the two-beam accelerator (TBA) driver was studied.